2018
DOI: 10.18632/oncotarget.25103
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institution analysis of racial disparity among African-American men eligible for prostate cancer active surveillance

Abstract: There is a significant controversy on whether race should be a factor in considering active surveillance for low-risk prostate cancer. To address this question, we analyzed a multi-institution database to assess racial disparity between African-American and White-American men with low risk prostate cancer who were eligible for active surveillance but underwent radical prostatectomy. A retrospective analysis of prospectively collected clinical, pathologic and oncologic outcomes of men with low-risk prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…In this study, the AA race was a significant predictor of pathological upgrading and upstaging (OR 1.2, 95% CI 1.1-1.3, p < 0.01). Despite these findings, other studies have not found a significant association between black race and pathological upgrading or upstaging [13,[19][20][21]. A major limitation of these studies is underrepresentation of AA men with the largest study including 355 AA men.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the AA race was a significant predictor of pathological upgrading and upstaging (OR 1.2, 95% CI 1.1-1.3, p < 0.01). Despite these findings, other studies have not found a significant association between black race and pathological upgrading or upstaging [13,[19][20][21]. A major limitation of these studies is underrepresentation of AA men with the largest study including 355 AA men.…”
Section: Discussionmentioning
confidence: 92%
“…Longstanding dogma based on epidemiologic data has posited that African American men have a higher incidence of advanced disease. However, multiple large series have shown that rates of upgrading or upstaging among men with low‐risk cancer characteristics are not affected by race . In addition, a recent massive cohort of men from SEER, the Veterans Administration, and Radiation Therapy Oncology Group trials showed that, after adjusting for access to care and standardization of treatment, men of African ancestry did not have an increased risk of cancer‐specific mortality .…”
Section: Type Of Bias Potentially Affecting Men and Physicians Regardmentioning
confidence: 99%
“…2 However, short-and long-term outcomes comparing AA race to CA race have been less consistent. At least four studies [3][4][5][6] have explored both short-and long-term outcomes in low-risk CA and AA men who underwent radical prostatectomy (RP). Two studies that examined biochemical recurrence (BCR)-free survival after RP showed no differences for CA vs AA men, 4,5 while two other studies did find a difference between CA and AA men.…”
Section: Introductionmentioning
confidence: 99%
“…At least four studies [3][4][5][6] have explored both short-and long-term outcomes in low-risk CA and AA men who underwent radical prostatectomy (RP). Two studies that examined biochemical recurrence (BCR)-free survival after RP showed no differences for CA vs AA men, 4,5 while two other studies did find a difference between CA and AA men. 3,6 In general, studies that found no difference in BCR-free survival across race also found few differences in adverse pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation